La lúdica en la comprensión lectora - Simbaña Fierro, Jessica Alexandra (2025)
The present research work entitled ''Playfulness in reading comprehension'' was to explore playful strategies for the reading comprehension of the students of the Unidad Educativa Dr. Nicanor Larrea León, since many of them found it difficult to understand a text because the strategies used by teachers are aligned with traditional educational practices. For this reason, it is necessary to implement playful strategies that awaken interest, motivation and strengthen learning. The development of the study was based on two categories, which were playfulness and reading comprehension. As for the methodology, a qualitative approach was implemented with the phenomenological method, a non-experimental design, with an exploratory and descriptive level of scope, according to the place was field, documentary and bibliographic. The research was carried out with a non-probabilistic purposive sample, made up of 32 students of 4th year of EGB, parallel B. Non-participant observation and unstructured interviews were used as techniques for data collection. In the first technique, the observation guide and the field diary were used as instruments; the guide was structured in three parameters and the field diary recorded perceptions, emotions and behaviors of the subjects of study. In the second technique, a questionnaire was designed with 10 open questions, related to each of the research categories directed to 4th grade EGB students. After selecting playful strategies for reading comprehension, the elaboration of playful processes and through the triangulation of data between the authors' theory, the students' opinions and the researcher's interpretation, it was found that implementing playful strategies in the teaching and learning process generates spontaneous participation and involvement of the students in the reading activities, given that in the development of the dynamics they experienced positive emotions such as joy, excitement, enthusiasm and fun, which awakened their interest and desire to learn.